Effectiveness of intracanal calcium hydroxide medicament in treating periapical lesions: a systematic review - Alghamdi, Faisal; Alkhattab, Omar (Journal of Stomatology, 2022)
Previous literature has shown that calcium hydroxide (CH) is a useful intracanal medicament for root canals. However, there is no conclusive evidence of its success rate in patients with periapical lesion. This study aimed to investigate the success rate and impact effect of endodontic treatment was done with CH in treating periapical lesions. We searched PubMed, Scopus, Web of Science databases, and Google Scholar as an engine to retrieve relevant interventional studies. Interventional studies were done on the success rate and impact effect of CH for patients with periapical lesion by endodontic treatment/retreatment approaches. Reviews, duplicate, animal studies, and other irrelevant studies were excluded. Two investigators independently following the (PRISMA) guidelines conducted the study selection and data collection process. The outcomes of this review were the status of the periapical lesion at the end of follow-up. We retrieved 8 studies with 481 participants. The success rate of CH in this review was 75.5%. The success rate of CH was 16% in patients with periapical/radicular cysts and 74% in patients with apical periodontitis after intracanal CH medicament. The post-treatment follow-up period showed a high success rate in patients with > 1-year post-treatment follow-up (62%) while the success was 30% in 6 month – 1-year post-treatment follow-ups. CH has a higher healing effect in lesions of ≤ 5 mm diameter than > 5 mm diameter (81.6% vs. 18.4%). Finally, intracanal CH has a clinically significant effect on the healing of periapical lesions. This review suggests orthograde root canal treatment with CH as an alternative to periapical/apical surgery.